Odkrywanie potencjału dziecka w pracy metodą projektów – praktyka nauczyciela przedszkola - Natalia Gozdalska (Problemy Wczesnej Edukacji)
The article describes experiences gained during work with the project approach with preschool children. These experiences are described in the context of the child’s scientific potential and the specificity of exploring the world in the 21st century. Conclusions from observations confirm the usefulness of the project approach in discovering and developing children’s potential in early education.